2006
DOI: 10.1103/physrevlett.96.257204
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Distribution of Magnetic Anisotropy in Thin Films Probed by Patterned Nanostructures

Abstract: We demonstrate that the switching field distribution (SFD) in arrays of 50 nm to 5 microm Co/Pd elements, with perpendicular anisotropy, can be explained by a distribution of intrinsic anisotropy rather than any fabrication related effects. Further, simulations of coercivity and SFD versus element size allow the distribution of intrinsic anisotropy to be quantified in highly exchanged coupled thin films where the reversal mechanism is one of nucleation followed by rapid domain wall motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
209
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 305 publications
(225 citation statements)
references
References 25 publications
13
209
3
Order By: Relevance
“…This discrepancy with the Stoner-Wohlfarth theory mostly originates from non uniform reversal modes that are initiated in low anisotropy regions like misorientated grains ͑and thermal activation͒. 5 Besides, as far as SFD is concerned, chemical interfaces represent the leading anisotropy term, however, the layering has very little irregularities or defects, so it is only a second order contribution to the SFD. In contrast the crystalline orientation of the grains is a second order anisotropy term, while misaligned grains and corresponding variations in anisotropy generate the dominating term to the SFD.…”
Section: -mentioning
confidence: 99%
See 2 more Smart Citations
“…This discrepancy with the Stoner-Wohlfarth theory mostly originates from non uniform reversal modes that are initiated in low anisotropy regions like misorientated grains ͑and thermal activation͒. 5 Besides, as far as SFD is concerned, chemical interfaces represent the leading anisotropy term, however, the layering has very little irregularities or defects, so it is only a second order contribution to the SFD. In contrast the crystalline orientation of the grains is a second order anisotropy term, while misaligned grains and corresponding variations in anisotropy generate the dominating term to the SFD.…”
Section: -mentioning
confidence: 99%
“…3,4 The SFD has multiple origins but intrinsic growth defects leading to anisotropy distribution has been shown to be a dominant one. [5][6][7][8] These defects include misorientated grains, grain boundaries, distribution of easy axis angle, variations in lattice stress, and variations in thicknesses or interface roughness in multilayers. Two recent investigations 7,8 indicate that misorientated crystalline grains are the major microstructural origin of SFD in ͑111͒ textured ͓Co/Pd͔ multilayers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] The magnetization reversal process in these systems usually involves the formation of vertically correlated stripe domains, through the entire multilayer film stack resulting from a competition between ferromagnetic (FM) exchange, anisotropy and dipolar energies. 1 The energy balance can be further tailored through the addition of Ru spacer layers with appropriate thicknesses, which establishes antiferromagnetic (AF) interlayer exchange coupling.…”
Section: Introductionmentioning
confidence: 99%
“…In fitting our data to this model we obtain a dimensionless energy barrier of ξ = 450, which is within 25% of that expected based on the volume, magnetization and anisotropy of the nanomagnet (ξ = M s H k V /(2kT ) = 360). Our previous results, as well as those of many other groups, have found energy barriers to reversal for long field [20][21][22][23] and long current pulses (> 100 ns) 9,10 to be only a small fraction of that expected for a macrospin, suggesting the reversal proceeds by subvolume nucleation 24,25 . For similar samples, we found that the energy barrier to reversal under long current pulses to be ≃ 60 k B T 9 , 1/6 the macrospin value.…”
Section: A→bmentioning
confidence: 94%